1983
DOI: 10.1152/ajpgi.1983.244.5.g515
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vagus, gastric inhibitory polypeptide, and HCl on gastrin and somatostatin release from perfused pig antrum

Abstract: The porcine antrum was isolated with the pancreas and perfused in vitro with an artificial medium supplemented with erythrocytes. The vagal innervation was preserved. Effluent was collected from the portal vein as well as from a vein directly draining the antrum. Electrical vagal stimulation increased gastrin output and inhibited somatostatin output. Intraluminal hydrochloric acid had the opposite effect. Gastric inhibitory polypeptide (GIP) in physiological concentrations (90 and 450 pmol/l) increased somatos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 0 publications
2
22
0
Order By: Relevance
“…The difference in antral output would not be expected to be due to a wash-out phenomenon of different magnitude in the 2 groups, since the antral vein blood flow increased by the same mea sure in the adrenalectomized animals and in animals with intact adrenals. We may thus conclude, in agreement with in vitro studies [1,14], that the specific effect of vagal stim ulation is an inhibition of somatostatin re lease in the fundic area, and a stimulation in the antral area; the latter, however, is depen dent on the presence of the adrenals.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The difference in antral output would not be expected to be due to a wash-out phenomenon of different magnitude in the 2 groups, since the antral vein blood flow increased by the same mea sure in the adrenalectomized animals and in animals with intact adrenals. We may thus conclude, in agreement with in vitro studies [1,14], that the specific effect of vagal stim ulation is an inhibition of somatostatin re lease in the fundic area, and a stimulation in the antral area; the latter, however, is depen dent on the presence of the adrenals.…”
Section: Discussionsupporting
confidence: 91%
“…Somatostatin inhibits gastrin se cretion (for review, see [5]) and gastrin may stimulate somatostatin release [10]. Because of these findings and the intimate relation ship between antral G and D cells, it has been proposed that endogenous somatosta tin exerts a continuous restraint on gastrin release in a paracrine mode [3], Accordingly, it has been shown that gastrin and somatos tatin secretion generally show an inverse re lationship [11][12][13][14], In agreement with this hypothesis, increased pre-stimulatory out puts of somatostatin (during low and high intragastric pH) were associated with signifi cantly decreased gastrin responses to vagal stimulation in the present experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric acidification of the gastric an trum elevated plasma concentrations of so matostatin in man in accordance with pre vious observations in the dog [ 13] and in the pig [44], The concomitant suppression of plasma gastrin and gastric acid secretion is compatible with a physiological role for antrally released somatostatin. Additional sup port is derived from the inverse covariation of plasma somatostatin and gastrin through out individual experiments.…”
Section: Discussionsupporting
confidence: 87%
“…In the stomach, it acts as the final common pathway for several reflexes which inhibit gastrin in the antrum, and acid secretion in the corpus. Antral D-cells have apical microvilli and release somatostatin in response to luminal acid [86,87]. They are also activated by fasting [88], when there is no food to buffer the acid.…”
Section: Gastrin and Somatostatin: The Effect Of H Pylorimentioning
confidence: 99%